Method for preparing foam iron through electrochemical deposition method and foam iron
By plating iron and nickel on polyurethane foam by electrochemical deposition method, a three-layer structure of nickel and titanium-iron-nickel is formed, which solves the problems of poor stability and corrosion resistance of iron foam, and achieves high stability and oxidation resistance of iron foam, which is suitable for alternative precious metal foam materials in high-end fields.
Patent Information
- Application Number
- CN202411812623.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
Existing foam iron is poor in high-end applications, is not corrosion-resistant, and is not oxidative-resistant, and is difficult to replace precious metal foam materials.
Electrochemical deposition method is used to conduct conductive treatment on polyurethane foam, first plating iron and then nickel to form a three-layer structure of nickel and titanium-iron-nickel, enhancing the stability and oxidation resistance of the foam iron.
The protection iron is encapsulated with a three-layer structure of nickel, titanium-iron-nickel, which significantly improves the stability and oxidation resistance of foam iron, allowing it to effectively replace precious metal foam materials in high-end fields while reducing costs.
Smart Images

Figure CN119615305A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials and discloses a method for preparing foamed iron by electrochemical deposition and the foamed iron. Background Art
[0002] Iron foam is a lightweight, shock-resistant, and heat-insulating material with excellent performance. It is currently used primarily in building insulation, packaging protection, and landscape sculpture. Metal foams such as nickel, copper, and silver are primarily used in battery electrodes, fuel cell components, catalyst supports, and audio components. However, these materials are relatively expensive and unsuitable for large-scale use. Replacing these materials with inexpensive metal foams, such as iron foam, could address these issues. However, iron foam also suffers from poor stability in these applications, requiring improvements based on traditional iron foams to meet application requirements.
[0003] The current mainstream method for producing foamed iron is electrodeposition. Other methods mainly include powder metallurgy, slurry coating, foaming, dealloying, etc. However, the dealloying method requires the use of a large amount of acid and alkali, which will cause environmental pollution. The preparation efficiency of the powder metallurgy method is low, the pore-forming agent used is easy to remain, and the porosity of the finished product is poor. The slurry coating and foaming methods are prone to pore blocking. In comparison, the electrodeposition method can avoid the above-mentioned shortcomings. In addition, the structure and performance of the foamed iron produced by the electrodeposition method are closest to those of foamed precious metals such as nickel foam.
[0004] Therefore, the technical problem that needs to be solved in this case is: how to prepare foamed iron with low cost, good corrosion resistance, and the ability to replace foamed precious metals. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing foamed iron by electrochemical deposition, so as to achieve performance improvement of the foamed iron. By adding nickel plating to the iron plating layer, a foamed iron product with higher stability and stronger oxidation resistance is obtained. The foamed iron can replace foamed precious metals, effectively reducing costs and enabling its application in specific fields.
[0006] At the same time, the invention also discloses foamed iron obtained based on the method.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] A method for preparing foamed iron by electrochemical deposition, specifically comprising the following steps:
[0009] Step 1: Conducting electrical conductivity on polyurethane foam;
[0010] Step 2: Iron plating the polyurethane foam obtained in step 1 using an iron plating solution;
[0011] Step 3: nickel plating the product obtained in step 2 using a nickel plating solution;
[0012] Step 4: The nickel-plated sample is subjected to combustion, reduction, and sintering treatments, and then post-processed to obtain a finished foamed iron.
[0013] In the prior art, the foam metals used in high-end fields are generally precious metals, such as batteries, electrode components, etc., and are generally based on foam precious metals such as silver, nickel, and copper. The oxygen content of these precious metal materials does not increase significantly during long-term use. In the preliminary research of this application, it was found that the foam iron prepared by the traditional preparation method was greatly reduced in effect when applied to the same working environment; in further research, it was found that the working environment of battery electrodes is almost always acidic or alkaline, and the working environment of catalysts will be exposed to oxygen over a large area. Foam precious metals such as silver, nickel, and copper are extremely stable and have the characteristics of corrosion resistance and oxidation resistance. However, foam iron has poor stability, is not corrosion-resistant, and is not resistant to oxidation. In the same working environment, its structure is easily destroyed, resulting in poor performance, rather than performance changes caused by structural problems of the prepared foam iron itself.
[0014] Based on this discovery, the foam iron prepared by the present invention is nickel-plated on the outside of the iron-plated layer to form a three-layer structure with iron in the middle layer. This not only reduces the cost but also solves the problem that the foam iron is not resistant to corrosion and oxidation.
[0015] Preferably, the iron plating solution comprises the following components:
[0016] Ferrous chloride (FeCl2·4H2O): 200-550g / L;
[0017] Ferrous sulfate (Fe2SO4·7H2O): 10-50g / L;
[0018] Ammonium chloride (NH4Cl): 10-50 g / L;
[0019] Malonic acid (C3H4O4): 1-5 g / L;
[0020] Ascorbic acid (C6H8O6): 0.1~1.0g / L.
[0021] Preferably, the iron plating in step 2 has a pH of 1 to 1.6 and a temperature of 70 to 85° C.
[0022] The working electrode spacing is 60-100mm, and the current density during pre-plating is 10-60A / dm 2 The pre-plating amount during pre-plating is 100-200g / m 2 The current density during flat plating is 8 to 15 A / dm 2, flat plating to the set amount, the cathode should be charged when entering the tank and the conductive sponge should be flat before entering the tank; its electrode structure is double anode, where the anode is pure iron or low carbon steel and wrapped with an anode bag, the cathode hanger must be well insulated and the conductive sponge must be in full contact with the electrode, and the area ratio of the positive and negative electrodes is 1:1.2.
[0023] Preferably, the nickel plating solution comprises the following components:
[0024] Nickel sulfate (Ni2SO4·6H2O): 150-350g / L;
[0025] Nickel chloride (NiCl2·6H2O): 20-60 g / L;
[0026] Boric acid (H3BO3): 10-40g / L.
[0027] Preferably, the nickel plating in step 3 has a working pH of 3.6 to 4.2, a temperature of 30 to 50°C, and a current density of 3 to 8 A / dm 2 , the minimum plating amount is 120g / m 2 ; The working pole spacing is 60~100mm.
[0028] Preferably, the combustion in step 4 is carried out at a temperature of 300-400° C. for 30-60 min, or at a temperature of 550-700° C. for 30-60 min, in an atmosphere of a mixed gas of 1-5 vol% O 2 and 99-95 vol% N 2 .
[0029] Preferably, the reduction in step 4 is carried out at a temperature of 900-980° C. for 1-2 hours in an atmosphere of a mixed gas of 3-5% H 2 and 97 vol%-95 vol% N 2 .
[0030] Preferably, the sintering in step 4 is carried out at a temperature of 1050-1250° C. for 1-2 hours in a pure N 2 atmosphere.
[0031] Preferably, the polyurethane sponge in step 1 is a polyurethane sponge with a pore density of 80 to 130 PPI (pore density, i.e., the number of pores per inch) and a thickness of 0.5 to 1.8 mm. The conductive treatment adopts a PVD process, and a Ni film with a thickness of 200 to 300 nm and a Ti film with a thickness of 100 to 200 nm are successively deposited on the surface of the polyurethane foam.
[0032] In addition, a foamed iron is provided, which is obtained by the above-mentioned preparation method.
[0033] The beneficial effects of the present invention are:
[0034] The present invention plates nickel and titanium on polyurethane foam for conductivity treatment, then electroplates the main material iron, and finally plates nickel again to form a three-layer structure of nickel, titanium-iron-nickel, completely wrapping and protecting the iron to obtain foamed iron with enhanced stability, which can reduce costs while ensuring material performance.
[0035] In the preferred embodiment of the present invention, by optimizing the composition of the plating solution, the metal ions in the iron plating solution are only iron ions, and the metal ions in the nickel plating solution are only nickel. This ensures that other metal impurities will not be introduced due to electroplating, and also ensures high-efficiency electroplating. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1A is the SEM image of the sample in Example 1;
[0037] Figure 1B is the SEM image of the sample in Example 1;
[0038] Figure 2 This is the SEM image of the sample in Example 2;
[0039] Figure 3 This is the SEM image of the sample in Example 3;
[0040] Figure 4 This is the SEM image of the sample in Example 4;
[0041] Figure 5 This is the SEM image of the sample in Example 6;
[0042] Figure 6 This is the SEM image of the sample in Comparative Example 1. DETAILED DESCRIPTION
[0043] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0044] The commodity source information in each embodiment and comparative example is as follows:
[0045] Ferrous chloride, ferrous sulfate, nickel sulfate, nickel chloride: McLean AR grade;
[0046] Ammonium fluoroborate, vanadium pentoxide: MacLean 99.99% specification;
[0047] Ammonium chloride, malonic acid, boric acid, sodium dodecylbenzenesulfonate, sodium chloride: Xilong Scientific AR grade;
[0048] Vanadium trichloride: Thermo Fisher Scientific 97% specification;
[0049] Manganese chloride: Kermel reagent AR grade.
[0050] It should be noted that the technical solution of the present invention can be implemented through other commercially available products.
[0051] Example 1
[0052] 1. On a polyurethane sponge with a thickness of 1.2 mm and a pore density of 100 PPI, a Ni film with a thickness of 250 nm was first deposited by PVD (physical vapor deposition) method, and then a Ti film with a thickness of 150 nm was deposited.
[0053] 2. Prepare the plating solution as required:
[0054] Iron plating solution: ferrous chloride tetrahydrate 450g / L, ferrous sulfate heptahydrate 25g / L, ammonium chloride 25g / L, malonic acid 4g / L, ascorbic acid 0.2g / L;
[0055] Nickel plating solution: nickel sulfate hexahydrate 300g / L, nickel chloride hexahydrate 50g / L, boric acid 30g / L;
[0056] Before electroplating iron, the iron plating solution is activated and circulated to 80°C until the solution shows a clear green color. The Hall effect cell test shows a silvery white coating. The pH of the iron plating solution is 1.2. At the same time, the nickel plating solution is heated to 40°C, at which point the pH of the nickel plating solution is 3.8.
[0057] 3. Electrodeposition of iron: The conductive sponge is loaded on a special hanger and then 2 The current density is pre-plated for 4 minutes, and the pre-plating amount is 150g / m 2 , then 10A / dm 2 The current density of the main plating is 40min, and the main plating amount is 500g / m 2 ; The cathode should be charged when entering the tank and the conductive sponge should be flat before entering the tank; its electrode structure is a double anode, where the anode is pure iron or low carbon steel and is wrapped with an anode bag. The cathode hanger must be well insulated and the conductive sponge must be in full contact with the electrode. The area ratio of the positive and negative electrodes is 1:1.2, and the working electrode spacing is 80mm; after plating, the iron plating solution on the surface is cleaned with 2% hydrochloric acid solution, and then cleaned with secondary water to prepare for nickel plating.
[0058] 4. Electroplated nickel: Electroplated iron-plated semi-finished products at 5A / dm 2 The current density was set to 0.5 and the working electrode spacing was 80 mm for 5 minutes. After plating, the nickel plating solution on the surface was cleaned with 2% hydrochloric acid solution, and then washed with secondary water and dried at 105 °C.
[0059] 5. Heat-treat the dried semi-finished products in an atmosphere furnace: 350°C for 40 min and 650°C for 30 min in a 3vol% O2 and 97vol% N2 atmosphere, 950°C for 1 h in a mixed reducing atmosphere of 4vol% H2 and 96vol% N2, and 1150°C for 2 h in a nitrogen atmosphere, and then cool with the furnace (the furnace body can also be water-cooled to accelerate cooling after the temperature drops below 500°C).
[0060] 6. Roll the heat-treated sample to 0.5 mm, then trim and package to obtain the foamed iron product.
[0061] Example 2
[0062] 1. On a 0.5 mm 80 PPI sponge, a 200 nm thick Ni film was first deposited by PVD (physical vapor deposition) method, followed by a 100 nm thick Ti film.
[0063] 2. Prepare the plating solution as required:
[0064] Iron plating solution: 550g / L ferrous chloride tetrahydrate, 50g / L ferrous sulfate heptahydrate, 10g / L ammonium chloride, 5g / L malonic acid, 1g / L ascorbic acid;
[0065] Nickel plating solution: nickel sulfate hexahydrate 350g / L, nickel chloride hexahydrate 60g / L, boric acid 40g / L;
[0066] Before electroplating iron, the iron plating solution is activated and circulated to 70°C until the solution shows a clear green color. The Hall cell test shows a silvery white coating. At this point, the pH of the iron plating solution is 1. At the same time, the nickel plating solution is heated to 30°C, at which point the pH of the nickel plating solution is 3.6.
[0067] 3. Electrodeposition of iron: The conductive sponge is loaded on a special hanger and then 2 The current density is pre-plated for 8 minutes, and the pre-plating amount is 100g / m 2, Then at 8A / dm 2 The main plating time is 60 minutes and the main plating amount is 500g / m 2 ; The cathode should be charged when entering the tank and the conductive sponge should be flat before entering the tank; its electrode structure is a double anode, where the anode is pure iron or low carbon steel and is wrapped with an anode bag. The cathode hanger must be well insulated and the conductive sponge must be in full contact with the electrode. The area ratio of the positive and negative electrodes is 1:1.2, and the working electrode spacing is 60mm; after plating, the iron plating solution on the surface is cleaned with 2% hydrochloric acid solution, and then cleaned with secondary water to prepare for nickel plating.
[0068] 4. Electroplated nickel: Electroplated iron-plated semi-finished products at 3A / dm 2The current density was set to 0.5 and the working electrode spacing was 60 mm for 7 minutes. After plating, the nickel plating solution on the surface was cleaned with 2% hydrochloric acid solution, and then washed with secondary water and dried at 105 °C.
[0069] 5. Heat-treat the dried semi-finished products in an atmosphere furnace: 300°C for 60 min and 550°C for 30 min in an atmosphere of 1 vol% O2 and 99 vol% N2, 900°C for 2 h in a mixed reducing atmosphere of 3% volH2 and 97% volN2, and 1050°C for 2 h in a nitrogen atmosphere, and then cool with the furnace (the furnace body can also be water-cooled to accelerate cooling after the temperature drops below 500°C).
[0070] 6. Roll the heat-treated sample to 0.5 mm, then trim and package to obtain the foamed iron product.
[0071] Example 3
[0072] 1. On a 1.8 mm 130 PPI sponge, a Ni film with a thickness of 300 nm was first deposited by PVD (physical vapor deposition) method, and then a Ti film with a thickness of 200 nm was deposited.
[0073] 2. Prepare the plating solution as required:
[0074] Iron plating solution: ferrous chloride tetrahydrate 200g / L, ferrous sulfate heptahydrate 10g / L, ammonium chloride 10g / L, malonic acid 1g / L, ascorbic acid 0.1g / L;
[0075] Nickel plating solution: nickel sulfate hexahydrate 150g / L, nickel chloride hexahydrate 20g / L, boric acid 10g / L;
[0076] Before electroplating iron, the iron plating solution is activated and circulated to 85°C until the solution shows a clear green color. The Hall effect cell test shows a silvery white coating. The pH of the iron plating solution is 1.6. At the same time, the nickel plating solution is heated to 50°C, at which point the pH of the nickel plating solution is 4.2.
[0077] 3. Electrodeposition of iron: The conductive sponge is loaded on a special hanger and then 2 The current density is pre-plated for 2 minutes, and the pre-plating amount is 200g / m 2 , then 15A / dm 2 The main plating time is 30 minutes and the main plating amount is 500g / m 2; The cathode should be charged when entering the tank and the conductive sponge should be flat before entering the tank; its electrode structure is a double anode, in which the anode is pure iron or low carbon steel and is wrapped with an anode bag. The cathode hanger must be well insulated and the conductive sponge must be in full contact with the electrode. The area ratio of the positive and negative electrodes is 1:1.2, and the working electrode spacing is 100mm; after plating, the iron plating solution on the surface is cleaned with 2% hydrochloric acid solution, and then cleaned with secondary water to prepare for nickel plating.
[0078] 4. Electroplated nickel: Electroplated iron-plated semi-finished products at 8A / dm 2 The current density was set to 0.5 and the working electrode spacing was 100 mm for 3 minutes. After plating, the nickel plating solution on the surface was cleaned with 2% hydrochloric acid solution, and then washed with secondary water and dried at 105 °C.
[0079] 5. Heat-treat the dried semi-finished products in an atmosphere furnace: 400°C for 30 min and 700°C for 30 min in a 5vol% O2 and 95vol% N2 atmosphere, 980°C for 1 h in a mixed reducing atmosphere of 5vol% H2 and 95vol% N2, and 1250°C for 1 h in a nitrogen atmosphere, and then cool with the furnace (the furnace body can also be water-cooled to accelerate cooling after the temperature drops below 500°C).
[0080] 6. Roll the heat-treated sample to 0.5 mm, then trim and package to obtain the foamed iron product.
[0081] Example 4
[0082] Specifically refer to Example 1, except that the composition of the iron plating solution is: 350 g / L of ferrous chloride tetrahydrate, 25 g / L of ammonium chloride, 4 g / L of malonic acid, 1 g / L of vanadium trichloride, 3 g / L of manganese chloride, and 0.03 g / L of sodium dodecylbenzenesulfonate;
[0083] Example 5
[0084] Specifically refer to Example 1, except that the composition of the iron plating solution is: 450 g / L of ferrous chloride tetrahydrate, 10 g / L of ammonium fluoroborate, 15 g / L of sodium chloride, 10 g / L of manganese chloride, and 0.3 g / L of vanadium pentoxide;
[0085] Comparative Example 1
[0086] 1. On a 1.2 mm 100 PPI sponge, a 250 nm thick Ni film was first deposited by PVD (physical vapor deposition) method, followed by a 150 nm thick Ti film.
[0087] 2. Prepare the plating solution as required:
[0088] Iron plating solution: ferrous chloride tetrahydrate 450g / L, ferrous sulfate heptahydrate 25g / L, ammonium chloride 25g / L, malonic acid 4g / L, ascorbic acid 0.2g / L;
[0089] Before electroplating iron, the iron plating solution is continuously activated and circulated and heated to 80°C until the plating solution shows a clear green color. A Hall cell test can be used and the coating shows silvery white. At this time, the pH of the iron plating solution is 1.2.
[0090] 3. Electrodeposition of iron: The conductive sponge is loaded on a special hanger and then 2 The current density is pre-plated for 4 minutes, and the pre-plating amount is 150g / m 2 , then 10A / dm 2 The current density of the main plating is 40min, and the main plating amount is 500g / m 2 ; The cathode should be charged when entering the tank and the conductive sponge should be flat before entering the tank; its electrode structure is a double anode, where the anode is pure iron or low-carbon steel and is wrapped with an anode bag. The cathode hanger must be well insulated and the conductive sponge must be in full contact with the electrode. The area ratio of the positive and negative electrodes is 1:1.2, and the working electrode spacing is 80mm; after plating, the iron plating solution on the surface is cleaned with 2% hydrochloric acid solution, then cleaned with secondary water, and dried at 105℃.
[0091] 4. Heat-treat the dried semi-finished products in an atmosphere furnace: 350°C for 40 min and 650°C for 30 min in a 3vol% O2 and 97vol% N2 atmosphere, 950°C for 1 h in a mixed reducing atmosphere of 4vol% H2 and 96vol% N2, and 1150°C for 2 h in a nitrogen atmosphere, and then cool with the furnace (the furnace body can also be water-cooled to accelerate cooling after the temperature drops below 500°C).
[0092] 5. Roll the heat-treated sample to 0.5 mm, then trim and package to obtain the foamed iron product.
[0093] Performance testing
[0094] Micromorphology testing method: German Zeiss Sigma300 field emission scanning electron microscope;
[0095] Porosity test method: GB / T21650.3-2011;
[0096] Oxygen content test method: LECO-RO600 of LECO Company, USA;
[0097] The samples of each embodiment and comparative example were tested according to the above method. For specific test data, please refer to Table 1.
[0098] Table 1: Sample test data
[0099]
[0100]
[0101] Conclusion analysis:
[0102] It can be seen from the sample data of Examples 1 to 3 that the porosity of the foamed iron prepared by the electrochemical deposition method of the present invention is above 90%, and that of Example 2 even reaches 93.6%. In addition, the foamed iron prepared has an extremely high antioxidant effect. After three months of storage, the oxygen content of Example 1 changes from 87 ppm to 380 ppm, the oxygen content of Example 2 changes from 102 ppm to 320 ppm, and the oxygen content of Example 1 changes from 96 ppm to 347 ppm. The changes are very small, which is precisely due to the innovative nickel plating effect of the present invention.
[0103] Examples 4 to 5 replaced the composition of the iron plating solution on the basis of Example 1. The foamed iron products also had good porosity and antioxidant effects, but the efficiency of iron electrodeposition was reduced, and V, Mn, and Na impurities were present in the finished products, and nodules occurred.
[0104] Comparative Example 1, based on Example 1, omitted the nickel plating process. After three months of storage, the oxygen content of the resulting nickel foam soared from 125 ppm to 67,000 ppm, indicating severe oxidation and unsuitability for use in high-oxygen environments. This demonstrates that nickel plating significantly enhances the anti-oxidation properties of the iron foam.
[0105] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations within the meaning and range of equivalents of the claims are intended to be included therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
Claims
1. A method for preparing foamed iron by electrochemical deposition, characterized in that: The specific steps include: Step 1: Conducting electrical conductivity on polyurethane foam; Step 2: using an iron plating solution to plate the polyurethane foam obtained in step 1 with iron; Step 3: nickel plating the product obtained in step 2 using a nickel plating solution; Step 4: The nickel-plated sample is subjected to combustion, reduction and sintering treatments, and then post-processed to obtain a finished foamed iron.
2. The method according to claim 1, characterized in that The iron plating solution comprises the following components: Ferrous chloride: 200~550g / L; Ferrous sulfate: 10-50 g / L; Ammonium chloride: 10-50 g / L; Malonic acid: 1-5 g / L; Ascorbic acid: 0.1~1.0g / L.
3. The method according to claim 2, characterized in that In step 2, the pH of the iron plating solution is 1 to 1.6, the temperature is 70 to 85° C., and the working electrode spacing is 60 to 100 mm; When plating iron, pre-plating is performed first and then flat plating is performed; the current density during pre-plating is 10 to 60 A / dm 2 The pre-plating amount during pre-plating is 100-200g / m 2 The current density during flat plating is 8 to 15 A / dm 2 , flat plating to the set amount.
4. The method according to claim 1, characterized in that: The nickel plating solution comprises the following components: Nickel sulfate: 150-350 g / L; Nickel chloride: 20-60 g / L; Boric acid: 10-40g / L.
5. The method according to claim 4, characterized in that In step 3, the pH of the nickel plating solution is 3.6-4.2, the temperature is 30-50°C, and the current density is 3-8A / dm 2 The minimum plating amount is 120g / m 2 , the working pole spacing is 60~100mm.
6. The method according to claim 1, characterized in that The combustion operation described in step 4 is: The temperature is 300-400℃, keep warm for 30-60min; then increase the temperature to 550-700℃, keep warm for 30-60min; The atmosphere during the combustion operation is a mixed gas atmosphere of 1 to 5 vol% O2 and 99 to 95 vol% N2.
7. The method according to claim 1, characterized in that The reduction operation described in step 4 is as follows: the temperature is 900-980° C., and the temperature is kept for 1-2 hours; the reducing atmosphere is a mixed gas atmosphere of 3-5 vol% H2 and 97%-95 vol% N2.
8. The method according to claim 1, characterized in that The sintering operation described in step 4 is: the temperature is 1050-1250° C. for 1-2 hours, and the sintering atmosphere is N 2 atmosphere.
9. The method according to claim 1, characterized in that: The polyurethane sponge in step 1 is selected to have a pore density of 80 to 130 ppi and a thickness of 0.5 to 1.8 mm; The conductive treatment adopts PVD process, and a Ni film with a thickness of 200-300nm and a Ti film with a thickness of 100-200nm are deposited on the surface of the polyurethane foam.
10. A foamed iron, characterized in that: The method is adopted as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Composite material of foamed metal, and preparation method
CN101092718A
Foam iron and manufacturing method thereof
CN102634824A